Pediatric Migraine Prescription Patterns - J Gordon Millichap; John J Millichap (Pediatric Neurology Briefs Publishers, 2014)
Investigators at Boston Children's Hospital determined the migraine prescription patterns in 4839 patients, ages 2 to 17 years, treated over a 4-year period.